Management of fatty liver disease with vitamin E and C compared to ursodeoxycholic acid treatment - Galip ERSÖZ; Fulya GÜNŞAR; Zeki KARASU; Sinan AKAY; Yücel BATUR; Ulus Salih AKARCA (Turkish Journal of Gastroenterology, 2019)
-